1980
DOI: 10.1111/j.2042-7158.1980.tb13047.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of mortality by sulphinpyrazone after experimental myocardial infarction in the rat

Abstract: In the Anturan Reinfarction Trial (ART 1978). reinfarctions and, expecially, sudden cardiac deaths were less frequent among patients treated with sulphinpyrazone than among those receiving placebo medication. There is wide, general interest in elucidating the mechanism by which sulphinpyrazone brings about these protective effects. Although they are presumed to be in some way related to its platelet-stabilizing action, conclusive evidence is lacking and exactly how the two phenomena are linked is still very mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This has been shown in the dog (Povalski et al, 1980;Moschos et al, 1981), in the cat (Kelliher et al, 1980), and in the rat (Brunner et al, 1980;Lepran et al, 1981), although the drug was reported to be inactive in the pig (Staubli et al, 1984). Sulphinpyrazone has also been shown to protect animal hearts against some but not all of the biochemical and histological consequences of coronary artery occlusion (Kelliher et al, 1980;Povalski et al, 1980;Bolli et al, 1981;Innes & Wiseman, 1981;Moschos et al, 1981;Karmazyn, 1984).…”
Section: Introductionmentioning
confidence: 92%
“…This has been shown in the dog (Povalski et al, 1980;Moschos et al, 1981), in the cat (Kelliher et al, 1980), and in the rat (Brunner et al, 1980;Lepran et al, 1981), although the drug was reported to be inactive in the pig (Staubli et al, 1984). Sulphinpyrazone has also been shown to protect animal hearts against some but not all of the biochemical and histological consequences of coronary artery occlusion (Kelliher et al, 1980;Povalski et al, 1980;Bolli et al, 1981;Innes & Wiseman, 1981;Moschos et al, 1981;Karmazyn, 1984).…”
Section: Introductionmentioning
confidence: 92%
“…However, other investiga tors found that lidocaine and verapamil were active in inhibiting ventricular arrhythmias in both man [21] and dog [22]. When admin istered for 3 days to rats in a myocardial infarction model, sulfinpyrazone reduced the mortality rate of the animals, though the un derlying mechanism of action was unknown [23], Atenolol has been suggested to have value for preserving the ischemic myocar dium [24], We were not able to demonstrate any pro tective effect with urokinase at a dosage which did cause considerable lysis of venous thrombi in the rabbit (data not shown); de spite similar fibrinolytic and plasminogen activating actions of D and urokinase [25] the underlying mechanisms may be different.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of its beneficial effect is uncertain although it may be related to its ability to reduce platelet aggregation (Smythe et al, 1965), a phenomenon seemingly dependent on platelet cyclooxygenase inhibition which would reduce thromboxane A2 production (Ali & McDonald, 1977). Studies using experimental animal models have demonstrated that sulphinpyrazone protects the heart from various pathological insults including catecholamine administration (Karmazyn et al, 1981a;Innes & Weisman, 1981) as well as coronary artery ligation (Brunner et al, 1980;Innes & Weisman, 1981;Davenport et al, 1981) in vivo, although the mechanistic basis for this protection still remains obscure. Few studies have been done on in vitro preparations in which blood-borne agents such as platelets would not be contributing factors.…”
Section: Sulphinpyrazonementioning
confidence: 99%
“…The mechanism of this beneficial effect is uncertain although these trials were carried out because sulphinpyrazone is a potent inhibitor of platelet aggregation. In experimental animals sulphinpyrazone has been shown to protect against cardiac injury produced by coronary artery ligation by increasing collateral blood flow , reducing mortality (Brunner et al, 1980) and preserving histological integrity (Innes & Weismann, 1981). Sulphinpyrazone also protects against catecholamine-induced cardiac injury as manifested by a lower mortality, reduced cardiac enzyme release, maintenance of histological integrity and prevention of coronary vasoconstriction (Karmazyn et al, 1981a,b).…”
Section: Heart Perfusionmentioning
confidence: 99%